Efektivitas Ancaman Pidana Dalam Penegakan Kepatuhan Pajak - Muhammad Safar Fazri (Restitusi : Jurnal Riset Perpajakan, 2023)
Tax compliance is very important to maintain fiscal stability and support economic growth. This study looks at how effective criminal threats are as a law enforcement tool to increase tax compliance in Indonesia. By using a juridical-normative approach supported by empirical data, this study evaluates the extent to which criminal threats regulated in the Taxation Law can encourage taxpayers to fulfill their obligations. The research results show that although criminal threats have a deterrent effect, weak law enforcement, low taxpayer awareness, and ineffective supervision systems often make them ineffective. To increase tax compliance, this study suggests a combination of criminal sanctions, tax directives, and strengthening compliance incentives. These results support tax policy reform, resulting in a fairer and more sustainable system..